Electrical Engineering Priciples and Applications ( Sách photo) - R.Hambley Allan (American : Perason Prentice Hall, 2005)
- Ac and dc machines
- Basic circuit analysics and measurement
- Computer based instrumentation, including Lab view
- Computer-aided ciruit analysis (PSpice)
- Digital logic circuits
- Diode circuits
- Electronic ampilifiers
- Field effects and bipolar junction transistors
- First and second order transients
- Microcontrollers (68HC11)
- Operational ampiliers
- Resonance and frequency response
- Steady state ac circuits
- Transformers
This book covers circuit analysis, digital systems, electronics, and electromanchanics at a level appropriate for either electrical-engineering students in an introductory course or nonmajors in a surey course. The only essential prerequisites are basic physics and single-variable calculus. Teaching a course using this book offers opportunities to develop theoretical and experimental skill and experiences in the following areas
Keywords: Electrical Engineering; Kỹ thuật điện; Vật lí ứng dụng